Organic matter, a critical factor to immobilize phosphorus, copper, and zinc during composting under various initial C/N ratios. (October 2019) - Wang, Lixia; Li, Yingxin; Prasher, Shiv O.; Yan, Baixing; Ou, Yang; Cui, Hu; Cui, Yanru
Highlights: Composting decreased the bioavailability of Cu, Zn and the mobility of P. Degradation of organic matter controlled redistribution of Cu, Zn and P fractions. A C/N ratio of 22 most effectively reduced the mobility of Cu and P. Zn fractions was unaffected by chemical parameters during compost. Abstract: The status of heavy metals and the P fractions in compost affects their environmental risk. The present study investigated the effects of different initial carbon to nitrogen (C/N) ratios (15, 22, 27) on redistribution of Cu, Zn, and P fractions during composting. The results showed that the composting process transformed Cu, Zn and P from mobile fractions to more stable fractions. Compost with an initial C/N of 22 showed the most effective immobilization of Cu, Zn and P because of yielding greatest degree of polymerization. Multivariate statistical analysis identified organic matter as the most critical factor for explaining the redistribution of Cu, Zn, and P fractions in composting. However, the degree of organic matter degradation (organic matter content and Humic acid/Fulvic acid) better explained the change of bioavailability factor for Cu and the mobility of P during composting. This research provided guidance for providing technology to reduce environmental risk in compost.